Hubungan Antara Keluarga dan Peer Group (Teman Sebaya) dengan Perilaku Cyberbullying pada Peserta Didik SMA Negeri di Kabupaten Luwu - Sumarlin Sumarlin (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2019)
The study aimed to determine the relationship between family and peer group to the cyber bullying behavior in public high school at Luwu Regency. The study used quantitative approach with questionnaire as the research instrument which the statements are the development of the theory and arranged in the operational concept. Based on the aim, the study applied correlation research with sixty samples that were taken from six public high schools at Luwu. The data were analyzed based on statistical analysis namely inferential statistic. Therefore the hypothesis testing and correlation test between variables are carried out. The significance level used was 5%. Based on the contingency coefficient correlation test, the value of ρ =, 000 was obtained, which showed that the correlation between peer support and cyber bullying behavior in high school students in Luwu Regency was statistically significant. The correlation value of 500 indicates positive correlation with moderate correlation strength. In conclusion, if family and peer group do not support cyber bullying behavior, it will further reduce high school students in getting cyber bullying.